2009
DOI: 10.1158/1055-9965.epi-08-1082
|View full text |Cite
|
Sign up to set email alerts
|

The Changing Incidence of In situ and Invasive Ductal and Lobular Breast Carcinomas: United States, 1999-2004

Abstract: Background: National incidence rates for lobular and ductal breast cancers have not been available previously. Evidence suggests that the increased risk of breast cancer associated with combined hormone replacement therapy use is higher for invasive lobular cancers (ILC) than for invasive ductal cancers (IDC). This study provides U.S. incidence rates for these histologic types for both in situ and invasive cancers and assesses changes in the incidence of these cancers over time. Methods: Data for this study in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
50
1
2

Year Published

2009
2009
2017
2017

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 90 publications
(58 citation statements)
references
References 38 publications
5
50
1
2
Order By: Relevance
“…Lobular cancers have also been postulated to be particularly sensitive to hormonal stimulation. While a few investigators have reported larger recent decreases in incidence for lobular cancers than for ductal cancers [14,20], we found no evidence of a different incidence pattern for the small subgroup of lobular carcinomas available for analyses in the present study.…”
Section: Ddd/1000contrasting
confidence: 93%
“…Lobular cancers have also been postulated to be particularly sensitive to hormonal stimulation. While a few investigators have reported larger recent decreases in incidence for lobular cancers than for ductal cancers [14,20], we found no evidence of a different incidence pattern for the small subgroup of lobular carcinomas available for analyses in the present study.…”
Section: Ddd/1000contrasting
confidence: 93%
“…This increase is also observed globally [61]; our data in relation to the increase of the non-infiltrating forms are very coincident with those reported in a US series that reported a fivefold increment of the frequency of non-infiltrative forms, mainly ductal, in the past 25 years [62,63]. Pure DCIS accounts for 15 to 20% of breast cancers compared with only 5% of cases before the advent of breast cancer screening [64,65].…”
Section: Morphologysupporting
confidence: 90%
“…With advances in breast cancer screening and mammography, cancer registries now indicate that DCIS represents close to 20% of the breast carcinomas diagnosed in the United States (38,39). DCIS itself is noninvasive, but cancer recurring after DCIS treatment is often invasive.…”
Section: Discussionmentioning
confidence: 99%